Improvement of the enterprise management system - Sviatnenko, Viktoriia (Technology audit and production reserves, 2020)
The object of this research is the enterprise management system with its subsystems. In the course of the research the methods of logical generalization and analysis were used in the study of literary sources on the subject of the research. And also methods of comparative analysis – at research of components of the enterprise and grouping management system – at selection of homogeneous groups on the basis of division of the management system into subsystems and at association of investigated subsystems into private collections on essential for them features. Tabular means were also used at displaying various approaches to consideration of variants of structural elements of enterprise management system. In the article the variants of interpretation of the essence of the concept «control system of enterprise» and approaches of different authors to the definition of the components of this system are considered. The selection of information about the list of enterprise management system components from publicly available scientific and electronic sources was carried out. As a result of indication of the main factors, conditions and risks, in which the enterprises function, it is recommended to include the following interrelated subsystems into the enterprise management system: planning; informational; operating; marketing; logistic; commercial; financial; social; innovative; investment; risk-management; controlling. It is also noted that the proposed list of subsystems will ensure the competitiveness of the enterprise in a complex and constantly changing economic environment. In addition, it is recommended to take into account changes in the role and weight of each subsystem in the overall management system of the enterprise depending on changes in external and internal environment factors, strategic goals of the enterprise, the level of use of modern technology, various risks and the like. Special attention is paid to the subsystem of risk management, in particular: the description of risks at three levels of management is carried out, the main tasks of risk management and directions of work with risk management are specified. Creation and use of the given subsystem will allow to increase efficiency of enterprise management system and will promote more rational use of own resources, qualitative control of expenses, minimization of risks connected with acceptance of administrative decisions.